Evaluation of real-time nutrient analysis of fertilized raspberry using petiole sap - Lu, Qianwen; Miles, Carol; Tao, Haiying; DeVetter, Lisa (Frontiers in Plant Science, 2022)
The time delay in receiving conventional tissue nutrient results has led to the interest of red raspberry (Rubus idaeus L.) growers into the use of rapid sap tests to provide real-time results to inform immediate nutrient management practices. However, sap analysis has never been tested in raspberry. The present work aimed to evaluate the relationship of petiole sap nitrate (NO3-), potassium (K+), and calcium (Ca2+) concentrations measured by compact ion meters with leaf tissue total nitrogen (TN), potassium (K), calcium (Ca) concentrations measured using conventional tissue nutrient analysis. The relationship of petiole sap NO3- and leaf tissue TN concentrations with plant growth and production variables was also explored. Fertilizer treatments of urea [46% nitrogen (N)] were surface applied to raised beds of established ‘Meeker’ floricane red raspberry plots at control, low, medium, and high rates (0, 34, 67, and 101 kg N ha-1, respectively) in 2019 and 2020. The experiment was arranged in a randomized complete block with three replications. The fourth fully expanded, whole leaves were collected from representative primocanes in mid- and late- July and August 2019 and 2020 (i.e., four sampling time points per year). At each sampling time point, a subsample of leaves was used for petiole sap analyses of NO3-, K+, and Ca2+ concentrations using compact ion meters, and conventional tissue testing of leaf tissue TN, K, and Ca concentrations, respectively. There were no interactions between N fertilizer rate and year nor between N fertilizer rate and sampling time. No significant differences were found due to N fertilizer rate for petiole sap NO3-, K+, Ca2+ nor leaf tissue TN, K, Ca concentrations. However, year and sampling time effects occurred in measured petiole sap and leaf tissue nutrient concentrations. Overall, petiole sap NO3- and Ca2+ were positively correlated to leaf tissue TN (r = 0.64) and Ca (r = 0.44) concentrations, respectively, while petiole sap K+ was negatively correlated to leaf tissue K concentration (r = -0.65). Future research is warranted as the interpretation of correlations between raspberry petiole sap and leaf tissue nutrient concentrations inconclusive due to an unexpected lack of a fertilizer response.